2011
DOI: 10.3959/2010-4.1
|View full text |Cite
|
Sign up to set email alerts
|

Regional And Watershed-Scale Coherence In the Stable-Oxygen and Carbon Isotope Ratio Time Series In Tree Rings Of Coast Redwood (Sequoia sempervirens)

Abstract: Coast redwood (Sequoia sempervirens) ecosystems are strongly influenced by the presence of summer marine fog, and variation in fog frequency is closely linked to climate variation in the NE Pacific region. Because oxygen isotope composition (d 18 O) of organic matter records distinct water sources (e.g. summertime fog vs. winter precipitation) and carbon isotopes (d 13 C) are typically sensitive to humidity and water status, it then follows that inter-annual variation in tree-ring isotope ratios, which are coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…Even if some authors have reported a high natural variability between individual δ 18 O series (e.g., Szymczak et al, 2012), important variabilities between individual δ 13 C series have been also documented for different deciduous and coniferous species in previous studies (Saurer et al, 1997b;Masson-Delmotte et al, 2004;Raffalli-Delerce et al, 2004;Roden et al, 2011). This phenomenon suggests a sensitivity of carbon isotopes to environmental conditions surrounding each sampled tree.…”
Section: Variability Of Carbon Isotopic Ratiosmentioning
confidence: 77%
“…Even if some authors have reported a high natural variability between individual δ 18 O series (e.g., Szymczak et al, 2012), important variabilities between individual δ 13 C series have been also documented for different deciduous and coniferous species in previous studies (Saurer et al, 1997b;Masson-Delmotte et al, 2004;Raffalli-Delerce et al, 2004;Roden et al, 2011). This phenomenon suggests a sensitivity of carbon isotopes to environmental conditions surrounding each sampled tree.…”
Section: Variability Of Carbon Isotopic Ratiosmentioning
confidence: 77%
“…[10] Tree cores for this study come from three separate sites in classic redwood habitat along 100 km of the Northern California coastline. The sites and trees used for this study are identical to those used by Roden et al [2009Roden et al [ , 2011. Excluded from the present work is one site from Sonoma, CA, located~300 km to the south, determined to be a statistical outlier from the three sites used here [Roden et al, 2011].…”
Section: Site Descriptionsmentioning
confidence: 99%
“…El análisis de serie de tiempo de la especie abeto Douglas ayudaría a confirmar los eventos extremos pasados en patrones de circulación atmosférica, escasez de recursos hídricos e impacto socioeconómico en la población (Cerano et al, 2011;Návar & Lizárraga-Mendiola, 2013). Recientemente, el uso del análisis de series de tiempo, combinado con isótopos de madera, y la dendrocronología han demostrado ser útiles para describir la relación de la fisiología de los árboles y la variabilidad del clima de acuerdo con el aumento de CO 2 atmosférico (Monserud & Marshall, 2001;Roden, Johnstone, & Dawson, 2011;Swetnam & Lynch, 1993).…”
Section: Introductionunclassified
“…Time series analysis of tree species like Douglas-fir would also help to confirm extreme past events in atmospheric circulation patterns, water resources shortage, and its socioeconomic impact on the population (Cerano et al, 2011;Návar & Lizárraga-Mendiola, 2013). More recently, the use of time series analysis combined with wood isotopes and dendrochronology have showed to be useful to describe the relationship of tree physiology and climate variability according to increased atmospheric CO 2 (Monserud & Marshall, 2001;Roden, Johnstone, & Dawson, 2011;Swetnam & Lynch, 1993).…”
Section: Introductionmentioning
confidence: 99%